2019
DOI: 10.2337/dc19-1125
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Oxygen Supply and Use in Type 1 Diabetes, From Ambient Air to the Mitochondrial Respiratory Chain: Is There a Limiting Step?

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
2
17
0
Order By: Relevance
“…However, during exercise, an impairment in the utilization of O 2 at the tissue could also be involved in a reduction of exercise capacities. Previous research had found that patients with T1DM displayed blunted perfusion and oxygen extraction in active skeletal muscle at moderate-to-maximal exercise intensities (Tagougui et al, 2015;Heyman et al, 2020). Accordingly, a greater increase in heart rate, along with an increase in the percentage of relative VO 2 peak in children with T1DM compared to the healthy control found in this study, could be a compensatory adaptation to increase O 2 delivery to the exercising muscle.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, during exercise, an impairment in the utilization of O 2 at the tissue could also be involved in a reduction of exercise capacities. Previous research had found that patients with T1DM displayed blunted perfusion and oxygen extraction in active skeletal muscle at moderate-to-maximal exercise intensities (Tagougui et al, 2015;Heyman et al, 2020). Accordingly, a greater increase in heart rate, along with an increase in the percentage of relative VO 2 peak in children with T1DM compared to the healthy control found in this study, could be a compensatory adaptation to increase O 2 delivery to the exercising muscle.…”
Section: Discussionsupporting
confidence: 60%
“…This lower aerobic capacity in children with T1DM may be related to early defects in the delivery of blood via the microcirculation to the skeletal muscle. Additionally, it may contribute to impairments in complex IV capacity in the mitochondrial respiratory chain (Heyman et al, 2020). Capacity to transport and utilize oxygen affects skeletal muscle function and exercise capacities (Lanfranconi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This mutation results in the reduction of insulin release and insulin resistance and leads to persistent hyperglycemia, which in turn causes mitochondrial dysfunction and reduces insulin release [22]. Muscle biopsies of diabetic patients have revealed abnormal mitochondrial metabolism and reduced mitochondria quantity [23,24].…”
Section: Regulating the Mitochondria To Against Diabetes And Itsmentioning
confidence: 99%
“…A recent meta-analysis highlighted the presence of early endothelial dysfunction in these patients, without overt vascular complications [3]. This dysfunction can even appear in response to day-to-day whole-body aerobic exercise, specifically at the level of microvessels close to active skeletal muscle [4][5][6]. Understanding the mechanisms involved in blunted muscle microvascular reactivity to exercise in uncomplicated type 1 diabetes is of great clinical relevance.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the mechanisms involved in blunted muscle microvascular reactivity to exercise in uncomplicated type 1 diabetes is of great clinical relevance. As such, in addition to possible longterm effects on primary determinants of diabetes complications, impaired blood supply to skeletal muscle may be involved in lower aerobic fitness [4][5][6], a strong predictor of cardiovascular mortality [7].…”
Section: Introductionmentioning
confidence: 99%